(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
As a result of the influence of phytoplasma genes in cotton fiber extension, a new phenomenon has been identified, proven by the RNA detection method. About 1000 new genes, marker lux have been created, which are associated with the quality of fiber, resistance to diseases and early riscopsy. With the use of gene-dot technology, high yielding potato varieties and cold and droughtresistant cotton lines were created. The center publishes over 200 scientific papers, including over 80 foreign publications, and 8 monographs published abroad. Practical: Scientific proposals and practical recommendations developed as a result of the study are used to study the optical properties of cotton fiber. Application area: Mining is widely used in industrial scientific centers.